The Christian Ethics of Norman Thomas, Socialist - Weber, Leonard J. (My University, 1974)
As a case study in Christian ethics, this thesis is an investigation of Norman Thomas' Christian social ethics, its background, its explicit presentation, and its continuing importance after Thomas abandoned other aspects of Christianity. The study focuses primarily on the values and ethical principles expressed in Thomas' social philosophy, during his year as Presbyterian minister and later as Socialist Part leader. This examination of his social thought is presented by a consideration of the social ethics of the Protestant Social Gospel tradition and the entire study concludes with relections on Thomas place in the history of Christian social ethics. The study makes it abunduntly clear that Norman Thomas, as a Christian minister, was part of the Protestant Social Gospel tradition that sought to establish the Kingdom of God on earth in America and that, by the twentieth century, had come to see that the Kingdom as characterized by peace, socialism, and individual freedom. Even more important, the analysis of Thomas' later social philosophy reveals that he continued throughout his later life to adhere to the same social goals and ethical principles that had been at the heart of his understanding of Christianity. With the rejection of his earlier notion of a God who intervenes on the side of right, Thomas was no longer so able to take absolute stands, but the entire approach of his political work remained ethical and the values were the very same ones that had characterized his Christian days. While it has been widely though that Thomas' mature social philosophy reflected some of his earlier Christian ethical principles in his socialism has not been examined prior to this thesis. Norman Thomas' social ethics was considerably closer in character to the social ethics of perennial Christian theology (for example, Thomas Aquinas) than to that of orthodox Protestantism. This is the conclusion reached in relating Thomas' thought to other forms of Christian social ethics; it may shed some light on the likelihood of persons from particular traditions finding Thomas' socialism compatible with their theological views.
Keywords: Religion; Religion